Smoothing along Frequency in Online Neural Network Supported Acoustic Beamforming - Heitkaemper, Jens; Heymann, Jahn; Haeb-Umbach, Reinhold (ITG 2018, Oldenburg, Germany)
We present a block-online multi-channel front end for automatic speech recognition in noisy and reverberated environments. It is an online version of our earlier proposed neural network supported acoustic beamformer, whose coefficients are calculated from noise and speech spatial covariance matrices which are estimated utilizing a neural mask estimator. However, the sparsity of speech in the STFT domain causes problems for the initial beamformer coefficients estimation in some frequency bins due to lack of speech observations. We propose two methods to mitigate this issue. The first is to lower the frequency resolution of the STFT, which comes with the additional advantage of a reduced time window, thus lowering the latency introduced by block processing. The second approach is to smooth beamforming coefficients along the frequency axis, thus exploiting their high interfrequency correlation. With both approaches the gap between offline and block-online beamformer performance, as measured by the word error rate achieved by a downstream speech recognizer, is significantly reduced. Experiments are carried out on two copora, representing noisy (CHiME-4) and noisy reverberant (voiceHome) environments.

Integration neural network based beamforming and weighted prediction error dereverberation - Drude, Lukas; Boeddeker, Christoph; Heymann, Jahn; Kinoshita, Keisuke; Delcroix, Marc; Nakatani, Tomohiro; Haeb-Umbach, Reinhold (INTERSPEECH 2018, Hyderabad, India)
The weighted prediction error (WPE) algorithm has proven to be a very successful dereverberation method for the REVERB challenge. Likewise, neural network based mask estimation for beamforming demonstrated very good noise suppression in the CHiME 3 and CHiME 4 challenges. Recently, it has been shown that this estimator can also be trained to perform dereverberation and denoising jointly. However, up to now a comparison of a neural beamformer and WPE is still missing, so is an investigation into a combination of the two. Therefore, we here provide an extensive evaluation of both and consequently propose variants to integrate deep neural network based beamforming with WPE. For these integrated variants we identify a consistent word error rate (WER) reduction on two distinct databases. In particular, our study shows that deep learning based beamforming benefits from a model-based dereverberation technique (i.e. WPE) and vice versa. Our key findings are: (a) Neural beamforming yields the lower WERs in comparison to WPE the more channels and noise are present. (b) Integration of WPE and a neural beamformer consistently outperforms all stand-alone systems.

Investigation of the impact of a wireless Fog Warning System with respect to road traffic on a highway - Outay, Fatma; Ahmar, Absar-Ul-Haque; Kamoun, Faouzi; Yasar, Ansar-Ul-Haque; Sommer, Christoph; Jabeur, Nafaa; El-Amine, Samar (Personal and Ubiquitous Computing)

Data-Centre Traffic Optimisation using Software-Defined Networks - Schwabe, Arne

Optimization-based material design of tailored stacked hybrids for further improvement in lightweight car body structures - Camberg, Alan Adam; Tröster, Thomas (HYBRID - MATERIALS AND STRUCTURES 2018 - PROCEEDINGS)

The Bonding Situation in the Dinuclear Tetra-Hydrido Complex [{5CpFe}2(μ-H)4] Revisited by Hard X-Ray Spectroscopy - Burkhardt, Lukas; Mueller, Carsten; Groß, Oliver A.; Sun, Yu; Sitzmann, Helmut; Bauer, Matthias (Inorganic Chemistry)

Pure Nash equilibria in restricted budget games - Drees, Maximilian; Feldotto, Matthias; Riechers, Sören; Skopalik, Alexander (Journal of Combinatorial Optimization)
In budget games, players compete over resources with finite budgets. For every resource, a player has a specific demand and as a strategy, he chooses a subset of resources. If the total demand on a resource does not exceed its budget, the utility of each player who chose that resource equals his demand. Otherwise, the budget is shared proportionally. In the general case, pure Nash equilibria (NE) do not exist for such games. In this paper, we consider the natural classes of singleton and matroid budget games with additional constraints and show that for each, pure NE can be guaranteed. In addition, we introduce a lexicographical potential function to prove that every matroid budget game has an approximate pure NE which depends on the largest ratio between the different demands of each individual player.

Bestimmung von Nanopartikeleigenschaften eines Aerosols - Schmid, Hans-Joachim; Rasche, David
Zusammenfassung: Bei einem Verfahren und einer Vor- richtung zur Bestimmung von Nanopartikeleigenschaften ei- nes nanopartikelbeladenen Aerosols (17), mit einer Test- kammer (1) zur Bestimmung der Nanopartikeleigenschaften des Aerosols (17), wobei die Testkammer (1) einen Aero- soleinlass (9) zum Einleiten des Aerosols (17) und ein Hül- lenluftstromeinlass (10) zur Einleitung eines Hüllenluftstroms (16) aufweist, die Oberseite (2) und die Unterseite (3) der Testkammer (1) jeweils eine flächige Elektrode (4, 5) auf- weist, so dass zwei im Abstand zueinander angeordnete Elektroden (4, 5) bereitstehen, zwischen denen ein elektri- sches Feld (6) erzeugbar ist, soll ein kompaktes Messgerät für die Vermessung der Eigenschaften von Aerosolnanopar- tikeln zur Verfügung gestellt werden, bei dem es ermöglicht wird, im selben Gerät die zweidimensionale Verteilung be- züglich des aerodynamischen und des volumenäquivalen- ten Durchmessers zu bestimmen, wodurch eine Lösung ge- schaffen wird, die es ermöglicht Aussagen über die Größe, die Masse, die Form und die geometrische Struktur einer Partikel zu treffen. Dies wird dadurch erreicht, dass der Inhalt der Testkammer (1) in Rotation versetzt wird, wobei die Ro- tationsachse (18) parallel zum elektrischen Feld (6) verläuft.

Energiemanagement von Haushaltsgroßgeräten - Stille, Karl Stephan Christian

Evaluation von Taxonomien: Ein Literaturüberblick - Hoffmeister, Jiajia

Zweiseitige Märkte und Plattformökonomie in der Information Systems-Forschung - Ein klassifizierender Literaturüberblick - Valentin, Andreas

Das Konzept der Kreativität in der Wirtschaftsinformatik: Ein Literaturüberblick - Weigang, Jana

Schüler*innen mit sonderpädagogischem Förderbedarf im Förderschwerpunkt Lernen in inklusiven und exklusiven Settings – Befunde der BiLieF-Studie zu familiären Kontextfaktoren und Herkunftseffekten - Neumann, Phillip; Grüter, Sandra; Lütje-Klose, Birgit; Wild , Elke (Empirisch-pädagogische Forschung in inklusiven Zeiten. Konzeptualisierung, Professionalisierung, Systementwicklung)

Testing psychometric properties of the CFT 1-R for students with special educational needs - Heine, Jörg-Henrik; Gebhard, Markus; Schwab, Susanne; Neumann, Phillip; Gorges, Julia; Wild, Elke (Psychological Test and Assessment Modeling)
Keywords: BiLieF; Inklusion; sonderpädagogischer Förderbedarf; Grundschule; Wohlbefinden; Rollenausprägungen sonderpädagogischer Lehrkräfte

Übersicht über den Forschungsstand zur Wirkung inklusiver und exklusiver Beschulung - Neumann, Phillip (Basiswissen Lehrerbildung: Inklusion in Schule und Unterricht. Grundlagen in der Sonderpädagogik)

Professionalisierung für eine inklusive Schule - Lütje-Klose, Birgit; Neumann, Phillip (Basiswissen Lehrerbildung: Inklusion in Schule und Unterricht. Grundlagen in der Sonderpädagogik)

Schulische Inklusion durch Kooperation. Die Entwicklung inklusiver Kulturen, Strukturen und Praktiken - Lütje-Klose, Birgit; Neumann, Phillip (Kooperation)

Studium Frühpädagogik - Albers, Timm

Einstellungsmuster pädagogischer Kräfte zum Thema Integration von Kindern mit Fluchterfahrung in eine Kindertageseinrichtung - Hoeft, Maike; Abendroth, Sonja; Piossek, Anna-Maria; Albers, Timm (Frühe Bildung)
Frühe Bildung 2018.7:191-198

Inklusion Europäisch: Ein Peer Learning-Projekt an der Universität Paderborn, der Freien Universität Bozen und der Hochschule Oberösterreich - Albers, Timm; Stroot, Thea; Kordts-Freudinger, Robert; Steinbrück, Maxi (Peer Learning an Hochschulen)
Keywords: s2n; Scan2Net